2020
DOI: 10.1002/ece3.6997
|View full text |Cite
|
Sign up to set email alerts
|

In a comfort zone and beyond—Ecological plasticity of key marine mediators

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 104 publications
1
21
0
Order By: Relevance
“…copepodite stages should be incorporated into more advanced models in the near future, which is in accordance with the study of Renaud et al (2018) who defined size as the main proxy of calorific content of this genus. Species identification based exclusively on morphometry (prosome length), commonly used in the last decades of Arctic zooplanktonology (e.g., Kwasniewski et al 2003) may not correctly classify species, since some individuals described as C. finmarchicus were actually smaller individuals of C. glacialis, which was underlined during research of Balazy et al (2019) and confirmed by the recent molecular studies (Renaud et al 2018;Trudnowska et al 2020).…”
Section: Comments and Recommendationsmentioning
confidence: 99%
“…copepodite stages should be incorporated into more advanced models in the near future, which is in accordance with the study of Renaud et al (2018) who defined size as the main proxy of calorific content of this genus. Species identification based exclusively on morphometry (prosome length), commonly used in the last decades of Arctic zooplanktonology (e.g., Kwasniewski et al 2003) may not correctly classify species, since some individuals described as C. finmarchicus were actually smaller individuals of C. glacialis, which was underlined during research of Balazy et al (2019) and confirmed by the recent molecular studies (Renaud et al 2018;Trudnowska et al 2020).…”
Section: Comments and Recommendationsmentioning
confidence: 99%
“…Despite the fundamentally similar role that the different Calanus species play in the marine ecosystem, their size, lipid content, life cycles and phenology all differ, albeit to different extents (Swalethorp et al, 2011;Trudnowska et al, 2020). For example, C. glacialis is recognised as a capital breeder (Hirche and Kattner, 1993) and is more lipid rich than C. finmarchicus, which is considered to be an income breeder, with the potential for capital breeding when food conditions are poor (Plourde and Runge, 1993;Mayor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An easier method of identification is based on prosome length, since C. glacialis are typically larger than C. finmarchicus (Unstad and Tande, 1991;Hirche et al, 1994;Weydmann and Kwasniewski, 2008). However, this approach is also limited because of prosome length overlap of these congeners in regions such as the Greenland Sea, the Irminger Basin, Svalbard and the Norwegian coast (Lindeque et al, 2006;Parent et al, 2011;Gabrielsen et al, 2012;Nielsen et al, 2014;Choquet et al, 2018;Trudnowska et al, 2020). When morphological variation cannot unambiguously identify species, genetic variation may be used for taxonomic discrimination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, despite extensive spatiotemporal sampling, no hybrids were ever detected with InDels in a total of 6467 Calanus spp. individuals genetically analyzed across various studies (Nielsen et al 2014; Choquet et al 2017 a , 2020; Daase et al 2018; Basedow et al 2019; Trudnowska et al 2020). In addition, we also investigated the question of hybridization with > 37 k genome‐wide SNPs, in a limited number of samples from three sympatric locations, and no sign of introgression (genetic signature of hybridization) was detected (Choquet et al 2019).…”
Section: Introductionmentioning
confidence: 99%